1996
DOI: 10.1007/bf00009640
|View full text |Cite
|
Sign up to set email alerts
|

Thaparocleidus Jain, 1952, the senior synonym of Silurodiscoides Gussev, 1976 (Monogenea: Ancylodiscoidinae)

L. H. S. Lim

Abstract: Silurodiscoides Gussev, 1976, is considered a junior subjective synonym of Thaparocleidus Jain, 1952, based on priority. Hence 70 monogenean species assigned to Silurodiscoides, Parancylodiscoides, Wallagotrema and Urocleidus from Asian and Eurasian freshwater siluriformes are re-assigned to Thaparocleidus as new combinations. Wallagotrema indicus Singh & Sharma, 1992 is renamed Thaparocleidus sharmae nom. nov. The generic characteristics of Thaparocleidus are those of Silurodiscoides and the type-species is T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 7 publications
2
45
0
Order By: Relevance
“…mekongensis Gustiano et al, in press and P. sabahensis Gustiano et al, in press (Siluriformes, Pangasiidae). One has been previously described (see "Dis cussion" below) on Pangasius bocourti Sauvage, 1880 (T. vietnamensis Pariselle et al, 2002) and was found also on P. mekongensis, five are considered new (see descriptions below), their anatomy (soft and hard parts) complies with that of Tbaparocleidus Jain, 1952 (Monogenea, Ancylodiscoididae) as defined by Lim (1996) and Lim et al (2001) The morphology of hard parts is identical to T. hume rus n. sp. except for the penis which presents a distal third with a reduced diameter and a thin velum-like expansion, and for the sclerotised vagina which is shorter.…”
Section: Resultsmentioning
confidence: 89%
“…mekongensis Gustiano et al, in press and P. sabahensis Gustiano et al, in press (Siluriformes, Pangasiidae). One has been previously described (see "Dis cussion" below) on Pangasius bocourti Sauvage, 1880 (T. vietnamensis Pariselle et al, 2002) and was found also on P. mekongensis, five are considered new (see descriptions below), their anatomy (soft and hard parts) complies with that of Tbaparocleidus Jain, 1952 (Monogenea, Ancylodiscoididae) as defined by Lim (1996) and Lim et al (2001) The morphology of hard parts is identical to T. hume rus n. sp. except for the penis which presents a distal third with a reduced diameter and a thin velum-like expansion, and for the sclerotised vagina which is shorter.…”
Section: Resultsmentioning
confidence: 89%
“…Two species are represented by too few individuals to be conclusively described (from two to five individuals among the 988 worms collected). The four remaining species are considered new (see descriptions below), their anatomy (soft and hard parts) complies with that of the diagnosis of Thaparocleidus (Monogenea, Ancylodiscoididae) as defined by Lim (1996) and Lim et al (2001 Adults: 649 ± 121 (423-959) long, 103 ± 18.5 (66-145) wide at the level of the penis. Pharynx: 45 ± 7.4 (27-56) wide.…”
Section: Resultsmentioning
confidence: 99%
“…Seven m onogenean sp ecies1 w ere recorded from P. bocou rti, P. d ja m b a l and P. h y p o p h th a lm u s, all belonging to n a p a r o c l e i d u s (Ancylodiscoidinae, M onogenea) as defined by Lim (1996). Tw o have been 1 An eighth species was found on P. djam bal from the Indragiri River at Rengat (Riau province, Sumatra Island, Indonesia), but only four worms could be examined, it is too few to describe this new spe cies.…”
Section: Resultsmentioning
confidence: 99%